PENGARUH DURASI MENONTON KONTEN EDUKASI DI YOU TUBE TERHADAP BERPIKIR KRITIS ANAK SEKOLAH DASAR SDN 1 WAWOLEMO - Rohana Talia; Rahma Al Ifta; Ishak Bagea; Abubakar; Aspin Jhody; Tini (STKIP Subang, 2026)
This study aims to analyze the effect of YouTube educational content viewing duration on the critical thinking skills of elementary school students at SDN 1 Wawolemo. This study used a quantitative approach with an ex post facto design. The study population was all students, with a sample determined through purposive sampling technique, namely students who actively use YouTube as a learning medium. Data collection techniques used a questionnaire to measure viewing duration and a test to measure students' critical thinking skills. Data were analyzed using descriptive and inferential statistics, specifically simple linear regression tests. The results showed that the duration of watching educational content was in the moderate category, while students' critical thinking skills were in the moderate to high category. The regression test results showed a positive and significant effect between the duration of watching educational content on YouTube and students' critical thinking skills. These results indicate that YouTube can be utilized as an effective alternative learning medium when used appropriately. However, viewing duration needs to be controlled and balanced with the selection of quality content and guidance from teachers and parents to optimally impact students' cognitive development.